The atlas of untold stories - Brunsvold, Sara, 1979- (Revell, a division of Baker Publishing Group, 2025)
A literary journey beckons them . . . and may profoundly rewrite their stories. Chloe Vance, dreamer of the family, needs to tell her pragmatic mom, Edie, that she has accepted a low-paying art instructor role at a Christian school in Prague. Her older sister, Lauren--the "responsible one"--is doing all she can to hide the fact she's been fired for a foolish mistake and is desperately seeking her next career move. Meanwhile, Edie, estranged from her own sister following their mother's recent death, is frankly in no mood for anything else to change. The one thing they can all agree on? Life in books sure is easier to navigate than life in the real world. As the three women embark on a nine-day road trip to visit significant literary sites throughout America's heartland, they hope to find inspiration through the works and lives of literary greats. As they experience firsthand the adventure and wonder of the classics, they'll discover the value of being honest with themselves--and their family--about their losses and failures. Only then can they come to terms with their own needs and desires and find support from the most important women in their lives--each other.